The Role of SiapaPeduli.id in Realizing Family Health Resilience - Alfayyedl, Dody (Sakina: Journal of Family Studies, 2022)
This research aims to study the impact of the COVID-19 pandemic on family health resilience and the role of SiapaPeduli.id in realizing family health resilience. This research is included in the type of empirical research using a qualitative approach. This study obtained data from the field by means of interviews and documentation. Meanwhile, for processing data from the field using data editing, classification, verification, analysis, and conclusions. The research subjects used were employees of SiapaPeduli.id and registered patients of SiapaPeduli.id. The results of this study indicate that: (1) many families in Indonesia, especially the patients of SiapaPeduli.id, feel the bad impact when the COVID19 pandemic takes place, including basic needs that are increasingly difficult to obtain, reduced income, affected by the termination of employment, difficulty meeting health needs such as medicine, nutrition, and medical devices, difficulty finding work, and difficulty paying fees or expenses from the hospital. (2) The role of the SiapaPeduli.id philanthropic institution which aims to realize family health resilience has been realized, including helping the underprivileged and having health problems, making it easier for the community to access assistance with fast and convenient procedures, forms of assistance in the form of nutritional needs, medicines, financial donations for patient care needs, and making health insurance in collaboration with the government, Aiding in the treatment and care of patients in order for them to recover to a healthy state, as well as caring for people who have health and economic problems in order to create conditions for family health resilience.